Legal role of artificial intelligence in institutionalization of public governance - Snizhana, Balo; Khmelnytskyi , Andrii (Pressing Problems of Public Administration, 2023)
This article explores the legal role of digital systems in the institutionalization of public administration in the context of decentralization, with a focus on the role of artificial intelligence (AI) in state management processes. The objective of the article is to define the legal role of AI and organized computer systems in state management processes and public administration. It identifies the factors that contribute to or hinder the effectiveness of integrating digital systems into legal institutions and relationships in Ukraine, with a specific determination of their distinct legal status. The research adopts a neo-institutional approach to analyze the legal institutionalization in various spheres of public administration. The article examines factors and elements that limit the effectiveness of AI usage in legal institutions during the process of decentralization and redistribution of executive powers, as well as in building a new quality of interaction with citizens and civil society. This material can serve as a foundation for studying ways to intensify the involvement of AI-based engineering systems in legal institutions in various aspects of public administration. Ukrainian scholars are encouraged to actively research the opportunities and challenges associated with AI implementation in public administration. Firstly, it is crucial to investigate the legal framework regulating the utilization of AI in state structures and institutions. Active collaboration with human rights organizations and other stakeholders is essential to ensure compliance with transparent and ethical standards in AI utilization in governance. Additionally, researchers should provide recommendations on establishing mechanisms for monitoring and auditing the implementation of AI to ensure its efficiency and compliance with legislation. Such an approach will contribute to the successful institutionalization of public administration using AI and promote the development of a modern and efficient system of state governance in Ukraine.